Making the Gap Year a Reality: Six Issues for Consideration - Abdullah, Doria (International Higher Education, 2017)
Starting in 2017, Malaysia has introduced the gap year for students in public universities, where they are given the option to take a year off for industrial training, pursue their interests in the arts, or work on volunteering projects. The intention is for the students to gain exposure, discover their potential and develop intellectually. How might the country make the gap year a meaningful experience for its students? This article offers six issues for consideration.